2020
DOI: 10.3389/fonc.2019.01505
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Promotion and Distress Reduction Using a Mobile App-Based Community in Breast Cancer Survivors

Abstract: Physical activity (PA) enhancement and mental distress reduction are important issues in cancer survivorship care. Mobile technology, as an emerging method for changing health behaviors, is gaining attention from many researchers. This study aimed to investigate the effect of a mobile app-based community on enhancing PA and decreasing distress in breast cancer survivors. We conducted a non-randomized, prospective, interventional study that had a mobile community-later arm and mobile community-first arm. With a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…Of the 31 included studies, 14 were conducted in the United States [ 10 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], five in Australia [ 38 , 53 , 54 , 55 , 56 ], four in Republic of Korea [ 57 , 58 , 59 , 60 ], two each in Canada [ 61 , 62 ] and France [ 63 , 64 ], and one each in The Netherlands [ 65 ], Germany [ 66 ], Spain [ 67 ], and United Kingdom [ 68 ]. All studies were conducted between 2015 and 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 31 included studies, 14 were conducted in the United States [ 10 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], five in Australia [ 38 , 53 , 54 , 55 , 56 ], four in Republic of Korea [ 57 , 58 , 59 , 60 ], two each in Canada [ 61 , 62 ] and France [ 63 , 64 ], and one each in The Netherlands [ 65 ], Germany [ 66 ], Spain [ 67 ], and United Kingdom [ 68 ]. All studies were conducted between 2015 and 2020.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were conducted between 2015 and 2020. Sixteen of the included studies were RCT [ 38 , 40 , 42 , 44 , 46 , 47 , 48 , 49 , 51 , 52 , 53 , 56 , 61 , 64 , 65 , 69 ], whereas 12 studies employed a pre-post [ 41 , 43 , 45 , 50 , 54 , 55 , 59 , 60 , 62 , 63 , 67 , 68 ], and three studies applied a quasi-experimental design [ 57 , 58 , 66 ]. The study duration ranged from two weeks [ 55 ] to six months [ 41 , 45 , 46 , 48 , 51 , 54 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related technologies preceded but are now accelerated by the recent COVID-19 pandemic [ 114 ]. Studies have demonstrated the feasibility of implementing remote cancer survivorship care delivery in high-risk patients [ 115 , 116 , 117 ], setting the stage for the development of population-based CVD interventions in large cohorts of survivors at a fraction of the cost that in-person care requires. These efforts set the stage for innovative delivery of care that will encourage patients to be actively engaged in CVD prevention and treatment during and after cancer therapy.…”
Section: Next Stepsmentioning
confidence: 99%
“…The Distress Thermometer and Problem List (DT&PL) is widely used as a self-reporting tool for the screening of distress in patients with cancer. [14,15] The DT is a single-item, self-reporting instrument measuring the amount of distress experienced by patients within the last week, with a score ranging from 0 (no distress) to 10 (extreme distress). The PL groups various problems patients with cancer encounter after diagnosis into ve problem categories: practical, family, emotional, physical, and spiritual.…”
Section: Psychological Distress Assessmentsmentioning
confidence: 99%